'Download to delicious': Promissory themes and sociotechnical imaginaries in coverage of 3D printed food in online news sources. (October 2017) - Lupton, Deborah
Highlights: A sociocultural analysis of 3D food printing in global English-language online news reports. Five main promissory themes in reporting are identified: futuristic, creative, healthy, efficient, and sustainable. These themes contribute to sociotechnical imaginaries related to food processing and food consumption. Abstract: The fabrication of food products is one of the emergent uses of 3D printing technologies. The news media are important sources for framing the meanings of emerging technologies such as 3D food printing and introducing them to publics. In this article, I discuss the findings of an analysis of online news reporting of 3D printed food technology. A sociocultural perspective was adopted, in which the promissory themes contributing to broader sociotechnical imaginaries related to food and novel technologies were identified in the corpus of news stories examined. These imaginaries can be pivotal in framing collective ideas of where the futures of technologies lie. The analysis found that, unlike coverage of many other novel food technologies, the corpus of online news reports examined overwhelmingly framed food printing technologies in positive ways. Five major promissory themes were identified, portraying 3D printed food technologies as: futuristic; creative; healthy; efficient; and sustainable. These themes contributed to sociotechnical imaginaries that drew on a number of contemporary preoccupations related to food cultures: novelty, entertainment and leisure pursuits; convenience and time-saving; effective production and distribution; health and nutritional aspects; and environmental impacts and global food security.